1998
DOI: 10.1016/s0194-5998(98)70023-3
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography in the Evaluation of Pediatric Neck Infections

Abstract: In children, infections involving both the superficial and deep neck spaces are common. Children so affected typically present with fever, neck mass, neck stiffness, and, occasionally, airway compromise. Radiologic modalities used in the evaluation of neck infections include plain lateral neck radiography, ultrasound, computed tomography, and magnetic resonance imaging. All these modalities have proved useful in the treatment of such infections, specifically the decision to perform incision and drainage. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 15 publications
(17 reference statements)
2
37
0
2
Order By: Relevance
“…Another explanation is that increased prevertebral soft tissue thickness could be relevant for retropharyngeal and parapharyngeal abscesses in particular; this subset was not studied separately. Overall, in the 32 patients who underwent surgical exploration in this series, purulence or fluid was found in 28 (88%), which is consistent with the findings of other authors [5,6]. Twenty-three patients had frank purulence and five patients had thin turbid fluid at the time of surgical intervention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another explanation is that increased prevertebral soft tissue thickness could be relevant for retropharyngeal and parapharyngeal abscesses in particular; this subset was not studied separately. Overall, in the 32 patients who underwent surgical exploration in this series, purulence or fluid was found in 28 (88%), which is consistent with the findings of other authors [5,6]. Twenty-three patients had frank purulence and five patients had thin turbid fluid at the time of surgical intervention.…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that the added expense of CT is superceded by the improved diagnostic yield and sensitivity [1]. Wetmore et al found a 92% correlation between CT findings of a deep neck abscess and the presence of purulence during surgical drainage [5]. Our study attempted to determine whether specific CT characteristics of neck abscesses would be useful in determining the need for surgical drainage.…”
Section: Discussionmentioning
confidence: 91%
“…In differentiating deep neck abscesses from phlegmons, several large series have reported the false-positive rate to range from 8% to 25%. [7][8][9]21 Furthermore, Broughton 5 and Sichel et al 6 describe children who responded to treatment with intravenous antibiotics alone with significant CECT evidence of RAs defined by classic radiographic criteria of ring enhancement and large size. Many of the cases reported by Sichel and colleagues showed scalloped rim enhancement, thought by Kirse and Roberson 1 to be an important predictor of abscess formation.…”
Section: Commentmentioning
confidence: 99%
“…21 Thecon tras ted-en han cedCT scanshelpma kingthedif fe ren ti aldi ag no sisbet weenabs cessandcel lu li tis. 12 Ring-en han ce mentaround the cen tral lu cency is a cha rac te ris tic ra di o lo gicsignforanabs cess. 10 WeusedCTscans in173(39%)pa ti entstoexa mi neaf fec tedspa ces anddif fe ren ti a tebet we enabs cessandcel lu li tis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Ra di o lo gicas sess mentisfun da men talinidentif yingthelo ca ti onandex ten si onoftheoro fa ci al in fec ti ons.Com pu tedto mog raphy(CT),mag ne tic re so nan ceima ging,ort ho pan to mog raphyandultra so nog raphyareuse fulinthedi ag no sisofin fecti onsofthema xil lo fa ci alre gi on. [9][10][11][12] Se ve reoro fa ci alin fec ti onsareusu allypoly mic ro bi al,con sis tingofbothana e ro besandae ro bes. Themostcom monly iso la tedor ga nismsfromthe oro fa ci alin fec ti onsareStrep to coc cusspp.,Pep tostrep to coc cus spp., pig men ted or non-pig men ted Pre vo tel la spp.,Ve il lo nel la spp.,Lac to ba cil lus spp., Cory ne bac te ri um spp.andAc ti nomy ces spp.…”
Section: Orofacialinfections:aretrospective Studyof440patientsunclassified